Construction of quantum states by special superpositions of coherent states. (15th June 2015) - Adam, P; Molnar, E; Mogyorosi, G; Varga, A; Mechler, M; Janszky, J
Abstract: We consider the optimal approximation of certain quantum states of a harmonic oscillator with the superposition of a finite number of coherent states in phase space placed either on an ellipse or on a certain lattice. These scenarios are currently experimentally feasible. The parameters of the ellipse and the lattice and the coefficients of the constituent coherent states are optimized numerically, via a genetic algorithm, in order to obtain the best approximation. It is found that for certain quantum states the obtained approximation is better than the ones known from the literature thus far.